Amniotic membrane transplantation for the treatment of recurrent ulcerative keratitis due to herpes simplex virus - Drozhzhyna, Galina (2016)
Herpes simplex keratitis is one of the leading causes of infectious corneal blindness in the world. It remains latent in the human host after the primary infection and can be reactivated by many factors. When activated, it travels along the trigeminal nerve to the cornea, and causes recurrent infection which leads to corneal scarring. Clinically, preserved AM used as a basement membrane substitute has been applied successfully for the management of persistent epithelial defects with and without ulcerations. Furthermore, multilayered AMT has been described to be useful for the treatment of deep corneal ulcers, descemetoceles, and small corneal perforations. This report describes a case of herpes simplex keratitis treated by amniotic membrane transplantation that resulted in high visual acuity and the absence of keratitis recurrent during two years.